Tripeptide linked dispiro cyclotriphosphazene conjugates: Synthesis, molecular docking analysis of compounds binding within cancer cell line receptors and in vitro cytotoxic and genotoxic activities - Caliskan, Eray; Capan, Irfan; Tekin, Suat; Qaoud, Mohammed T.; Biryan, Fatih; Koran, Kenan; Gorgulu, Ahmet Orhan (Academic Press Inc Elsevier Science, 2024)
The novel dioxybiphenyl bridged-cyclotriphosphazenes (DPP) bearing tripeptide were synthesized and investigated for their molecular docking analysis, visualizing their binding profiles within various cancer cell line receptors and in vitro cytotoxic and genotoxic properties. The dipeptide compound (Tyr- Phe) was treated with various amino acids to obtain the tripeptide compounds (Tyr- Phe- Gly, Tyr- Phe- Ala, Tyr- Phe- Val, Tyr- Phe- Phe, and Tyr- Phe- Leu). These synthesized tripeptides were subsequently treated with DPP to obtain novel phosphazene compounds bearing tripeptide structures. As a result, the synthesis of target molecules with phosphazene compound in the center and biphenyl and tripeptide groups in the side arms was obtained for the first time in this study. Examining the cytotoxic studies in vitro of our newly synthesized compounds demonstrated the anticancer properties against four selected human cancer cell lines, including breast (MCF-7), ovarian (A2780), prostate (PC-3), and colon (Caco-2) cancer cells. The Comet Assay analysis determined that the cell death mechanism of most of the compounds with cytotoxic activity stemmed from the DNA damage mechanism. Among the compounds, the DPP-Tyr- Phe- Phe compound seems to have the best anticancer activity against the subjected cell lines (Except for A2780) with IC 50 values equal to 20.18, 72.14, 12.21, and 5.17 mu M against breast, ovarian, prostate, and colon cancer cell lines, respectively. For this reason, the molecular docking analysis was conducted for the DTPP compound to visualize its binding geometry and profile within the target enzyme 's binding site associated with the specific cancer cell line. The analysis revealed that the DTPP derivative exhibited an optimal binding conformation and characteristics within the target enzyme 's binding site, aligning well with the experimental data. Based on the data, these compounds are believed to be strong candidate molecules for both pharmaceutical and clinical applications.
Keywords: Cyclotriphosphazene; DNA damage; Phosphazene; Tripeptide; Cytotoxicity